Error analysis: A psycholinguistic study - Hay, G.B. (My University, 1981)
Despite seven to nine years of english language learning at school, a majority of Sri Lankan students continue to produce errors at the level of syntax, lexicology, semanices and at the broader leavels of communication in the second language. The purpose of the present study was to identify persistent error types and to trace possible sources of errors. In addition answers were sought to questions arising out of theoretical...